Uso del hábitat y pautas conductuales de Pyrocephalus rubinus y Tyrannus vociferans en el Parque Ecológico Xochimilco - Camacho García, Norma Angélica (Universidad Autónoma Metropolitana, 2013)
The structure and composition of vegetation directly affect foraging , reproduction , establishing territories and intra and interspecific interactions of birds. In this study we evaluated the agonistic behavior, reproductive and feed of Pyrocephalus rubinus and Tyrannus vociferans in a mosaic of vegetation in order to analyze the differences in behavior in different microhabitats and determine the relationship between vegetation and the different activities. The study site is dominated by Taxodium mucronatum, Salix bonplandiana and Bromus sp. 16 transects were established 150m long x 50m wide which included three plant associations. Of these ten transects are close to water bodies. P. rubinus was more abundant at sites dominated by T. mucrunatum while T.vociferans was more common at sites dominated by Salix bonplandiana and Bromus sp. A classification of transects based on observed behaviors indicated that P. rubinus uses central sites of the area with a significant amount of woodland for breeding and feeding. T. vociferans however, uses open sites from which performs aerial displays for food and make processions.; La estructura y la composición de la vegetación influyen directamente en la búsqueda de alimento, la reproducción, el establecimiento de territorios y las interacciones intra e interespecíficas de las aves. En el presente trabajo se evaluaron las conductas agonista, reproductiva y de alimentación de Pyrocephalus rubinus y Tyrannus vociferans en un mosaico de vegetación con el fin de analizar las diferencias de comportamiento en distintos microhábitats y determinar la relación entre la vegetación y las diferentes actividades. El sitio de estudio está dominado por Taxodium mucronatum, Bromus sp y Salix bonplandiana. Se establecieron 16 transectos de 150m de largo x 50m de ancho que incluyeron las tres asociaciones vegetales. De estos transectos diez están cercanas a cuerpos de agua. P. rubinus fue más abundante en los sitios dominados por T. mucrunatum mientras que T.vociferans fue más común en los sitios dominados por Salix bonplandiana y Bromus sp. Una clasificación de los transectos basada en las conductas observadas indicó que P. rubinus utiliza sitios centrales del área con una significativa cantidad de arbolado para reproducirse y alimentarse. T. vociferans en cambio, usa sitios abiertos desde los cuales realiza despliegues aéreos para obtener alimento y realizar cortejos.